2022
DOI: 10.1038/s41598-022-12577-8
|View full text |Cite
|
Sign up to set email alerts
|

5-Azacytidine increases tanshinone production in Salvia miltiorrhiza hairy roots through epigenetic modulation

Abstract: Recent studies have indicated strong connections between epigenetic modulation and secondary metabolites in plants. It is vital to understand the roles of epigenetics in the production of secondary metabolites. In this study, the inhibitor of DNA methylation 5-azacytidine (5-Az) was used on the hairy roots of the medicinal plant Salvia miltiorrhiza to investigate its effect on secondary metabolite production, gene expression, methylation levels in genomic DNA and promoter regions. Our results showed that the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Smi-miR5072 may participate in terpenoid backbone biosynthesis through regulating the enzyme gene acetyl-CoA C-acetyltransferase gene ( SmAACT ) [ 40 ]. Smi-miR7972 plays a role in tanshinone biosynthesis through regulating DEMETER-like DNA glycosylase 1 ( SmDML1 ), a gene associated with DNA methylation and demethylation in S. miltiorrhiza [ 54 , 58 ]. Smi-miR319, Smi-miR159, and Smi-miR828 regulate anthocyanin and phenolic acid biosynthesis through targeting a subset of SmMYB genes [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Smi-miR5072 may participate in terpenoid backbone biosynthesis through regulating the enzyme gene acetyl-CoA C-acetyltransferase gene ( SmAACT ) [ 40 ]. Smi-miR7972 plays a role in tanshinone biosynthesis through regulating DEMETER-like DNA glycosylase 1 ( SmDML1 ), a gene associated with DNA methylation and demethylation in S. miltiorrhiza [ 54 , 58 ]. Smi-miR319, Smi-miR159, and Smi-miR828 regulate anthocyanin and phenolic acid biosynthesis through targeting a subset of SmMYB genes [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, high concentrations of methylation inhibitors can lead to the yellowing and even death of plant organs [ 54 , 55 , 56 ]. Previous studies have shown that DNA methylation inhibitors in a certain concentration range can change DNA methylation levels and promote gene expression after treating rice, Arabidopsis , Salvia miltiorrhiza and strawberry [ 57 , 58 , 59 , 60 ]. In this study, four concentrations of 5-Aza-dC, 5 μM, 10 μM, 20 μM and 30 μM, were tested in a pretest study according to previous studies [ 61 , 62 ], and 20 μM of 5-Aza-dC was selected for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In plants such as medicinal plants, the production of secondary metabolites was found to be closely associated with 5mC methylation. 45 In tea plants, it had been reported that 5mC methylation involved in chilling response, 18 albino type, 46 ABA and indole accumulation in postharvest processing. 47,48 These studies implied that 5mC methylation plays an important role in stress response before and after harvest of tea and is involved in formation of tea quality.…”
Section: Association Of 5mc Methylation Change With Gene Expression I...mentioning
confidence: 99%